Diseño de espacio público en Naranjal aplicando métodos de actuación con criterio urbano a escala humana - Arias Saldaña, Maria José (2024)
In Naranjal, the current urban public spaces present flaws in architectural and functional aspects that affect the population, this being a determining factor for people not wanting to use them. In this regard, the design of an urban park with human-scale design criteria aims to improve the needs of comfort, safety and inclusion. This through spaces designed and adapted for different age ranges and needs of the people who visit the park. Likewise, important factors such as accessibility and connectivity, the incorporation of vegetation, and safety and comfort are taken into account to ensure a pleasant space. In the same way, active recreation areas are incorporated, such as sports fields, children's games and outdoor exercise. Passive recreation areas such as interactive trails and rest areas provide relaxation. On the other hand, it is taken into account that the urban furniture to be implemented has a comfortable and accessible size for all people, respecting scales and proportions. Likewise, meeting areas such as a plaza, restaurants and picnic areas that facilitate social interaction among residents. These elements will help create a pleasant and functional space, designed for people and their experience, promoting a sense of belonging for the community.